Seismic retrofitting method for steel structures by knee braces jointed by high hardness vises - Nakahara, Hiroyuki; Nan, Ding; Shimomura, Takato (Journal of Civil Engineering and Management, 2023)
The authors have developed a new method of seismic retrofit for steel structures by adding knee braces which is jointed to the existing structures by vises with screw bolts made of high hardness metal. The slipping strength of the connection had been studied through axial tensile test of steel coupons jointed by the vises. The features of the connection by the vise are easy setup and providing the strength as much as by the normal bolts joint. An experimental study had been conducted for the specimens of steel frames retrofitted by knee braces. The knee brace was jointed to the steel frames by the vises. Two types of failure modes were investigated. One was slipping behavior at the connection and the other was bucking behavior at the knee braces. The strengths of the specimens were estimated by the simple calculations for the two types of failure modes.First published online 30 November 2022